2017
DOI: 10.1093/mnras/stx2058
|View full text |Cite
|
Sign up to set email alerts
|

Extreme infrared variables from UKIDSS – II. An end-of-survey catalogue of eruptive YSOs and unusual stars

Abstract: We present a catalogue of 618 high amplitude infrared variable stars (1 < ∆K < 5 mag) detected by the two widely separated epochs of 2.2 µm data in the UKIDSS Galactic plane survey, from searches covering ∼1470 deg 2 . Most were discovered by a search of all fields at 30 < l < 230 • . Sources include new dusty Mira variables, three new CV candidates, a blazar and a peculiar source that may be an interacting binary system. However, ∼60% are YSOs, based on spatial association with star forming regions at distanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 284 publications
(276 reference statements)
1
34
0
Order By: Relevance
“…YSOs dominate the Galactic population of high amplitude near infrared variable stars (Contreras Peña et al 2014, 2017aLucas et al 2017). Given that our search was focussed on IRDCs we would therefore expect most of the 23 variable stars in Table 1 to be YSOs.…”
Section: Summary Of Variable Star Findingsmentioning
confidence: 98%
See 2 more Smart Citations
“…YSOs dominate the Galactic population of high amplitude near infrared variable stars (Contreras Peña et al 2014, 2017aLucas et al 2017). Given that our search was focussed on IRDCs we would therefore expect most of the 23 variable stars in Table 1 to be YSOs.…”
Section: Summary Of Variable Star Findingsmentioning
confidence: 98%
“…YSOs in the Galactic plane. All the YSO candidates lie in the "YSO region" of the W1 − W2 vs. W3 − W4 diagram that distinguishes YSOs from AGB stars, as defined separately by Koenig & Leisawitz (2014) and Lucas et al (2017), with the exception of source 2 in Table 1, see section 3.1. (We used the WISE All-Sky database to provide contemporaneous colours for this assessment).…”
Section: Summary Of Variable Star Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The longer exposure time for K s aims at increasing the likelihood of detecting young variables since several Galactic studies have shown that variability in this filter is common amongst young stars (e.g. Contreras Peña et al 2014;Lucas et al 2017). It also allows us to better probe high-extinction regions, where young stars are preferentially located.…”
Section: Complementary Datamentioning
confidence: 99%
“…This is especially powerful in the faint limits of optical and infrared surveys, where they are incomplete, and the young stars become blended with reddened background stars. In recent years, various variability surveys have used near-IR to unveil disk-bearing stars both in clusters and associations (e.g., Rice et al 2012;Wolk et al 2013;Meng et al 2019) as well as in the field (e.g., Lucas et al 2017). Recognizing the typical variability of disk-bearing stars requires determining the occurrence and prevalence of different variability mechanisms.…”
Section: Introductionmentioning
confidence: 99%